BERSIH MELAYANI UMAT HINDU MENUJU SUMBER DAYA MANUSIA BERKUALITAS (PERSPEKTIF FILSAFAT HINDU) - I KETUT SUBAGIASTA (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
This article entitled “The Clean Service of Human Mankind of Hindu Concern for Human Resources be Quality Perspective Philosophy of Hindu”. Main description of this article about honest service for enlightenment spiritual Hindu human mankind, the openness in creation young generation of Hindu, the allegiance in life of the household, the balanced in dynamic of reality of working, and persevering study in the period of the yong generation. Then described also about the become Hindu generation which be wide perception, become generation ready as competitor, become the generation of Hindu be skillful, become the Hindu generation the best prestige, and become the Hindu generation militant.